Prinsip Keadilan Pada Jual Beli Dalam Pandangan Al-Qur’an Dan Hadits - Eva Naila; Helmayanti; Siti Nabila Zahra; Navisya; Erwan Setyanoor (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
Buying and selling is part of economic activities that cannot be separated from human life, both in the past and in the present. In the view of Islam, buying and selling is an aspect of life that is grouped into muamalah issues, namely relationships between fellow humans that are regulated so that they remain fair and do not harm each other. With the view of the Qur'an and Hadith, we can find out how the principles of justice in buying and selling are applied. The principles of justice in buying and selling include honesty in conveying information, the willingness of both parties, as well as the prohibition of fraudulent practices (tadlis) and usury. All these values aim to make buying and selling run in a fair way and in accordance with Islamic teachings. In practice, these principles also include the need for an agreement without coercion, clarity of the object of the transaction (bayyinah), and fulfillment of the rights and obligations of each party. This research is important to provide a deeper understanding of Islamic business ethics in the contemporary context, especially in the midst of the development of the digital economy and the rise of online transactions that are prone to manipulation of information and exploitation of weak parties.